Bank lending and economic growth in Malaysia: revisited - Tuck, Cheong Tang (Universiti Utara Malaysia, 2003)
The present study has re-investigated the role of bank financing on Malaysian economic development by using the bounds testing approach proposed in Pesaran, et al. (2001). This study had covered the annual periods from 1960 to 1998. The findings of the study are as follows. First, contrary to a previous study [Tang, 2000], it was found that there was no long run relationship between the volume of bank lending and the real Gross Domestic Product (GDP). Second, a long run relationship had been observed between real GDP, and volume of bank lending after including real exports variable into cointegration system. This finding clearly shows, the potential bias of omission variables in bivariate specification. An interesting outcome of the study is the suggestion that bank financing is strongly led by a country's economic development in the long run. The estimated elasticity is 3.02. The study suggests that in order to support a sustainable economic growth in Malaysia, bank financing for the private sector will be necessary.